Reading in Colette: Domination, Resistance, Autonomy - Laurel Cummins (Studies in 20th & 21st Century Literature, 1996)
The act of reading on the part of Colette's characters reveals itself as a dynamic involving domination and resistance. A study of passages from two of her semi-autobiographical works, La Maison de Claudine and Sido, brings to light both a positively connoted model of reading, exemplified by the character 'Colette,' and a negatively connoted model, exemplified by the older sister Juliette. While Juliette approaches texts with no sense of self, and seeks instead to be defined by the texts she reads, 'Colette' remains in relation to texts and to the discourses they contain, and resists them. Gender complicates the process. Both father and mother intervene in 'Colette's' apprenticeship as reader. While the censorship that constitutes the father's intervention proves both debilitating and disempowering, the mother's modeling of reading as dialogue and resistance empowers 'Colette,' both as a reader and a female being.
Keywords: act of reading; Colette; character; characters; domination; resistance; semi-autobiographical; La Maison de Claudine; Sido; model of reading; positive; older sister; Juliette; negative; example; no sense of self; self; Gender; father; mother; apprenticeship; debilitating; disempowering; reading as dialogue; dialogue; reader; female; being